Implementasi Supervisi Klinis Sebagai Upaya Meningkatkan Kompetensi Pedagogik Guru dalam Melaksanakan Pembelajaran di SD Nogosari UPT PPK Imogiri Bantul - Hariyono Hariyono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
Teachers are professional educators. To carry out their duties in educating students, teachers must have sufficient competence. Teachers who have good competence are certainly also better able to carry out learning well, especially in pedagogical competence in implementing learning. There are still problems related to teacher teaching achievement. Teachers still have low pedagogical learning competencies. The objectives of this study are (1) to determine the implementation of clinical supervision as an effort to improve the pedagogical competence of teachers at SD Nogosari UPT PPK Imogiri Bantul, and (2) to improve the implementation of clinical supervision as an effort to improve teacher pedagogical competence at SD Nogosari PPT Imogiri Bantul. This research is a school action research. The subjects in this study were elementary school teachers from Nogosari UPT PPK Imogiri Bantul in the academic year 2017/2018. Data collection is done through observation. Data analysis was performed through descriptive analysis. Clinical supervision is carried out through 3 stages, namely the initial meeting, observation, and final meeting stages. After the implementation of the two cycle of action research there was an increase in pedagogical competence in implementing teacher learning. The results of assessing pedagogical competence in implementing teacher learning before implementing action have not yet reached the minimum grade limit on the majority of teachers. After the first cycle, completeness obtained was 62.5% with an average value of 72.38. In the first cycle, the lowest value was 64.29 and the highest value was 82.38. This is not as expected because the expected results are at least the expected completeness> 80%, with teacher scores> 68.75. In cycle II, the completeness obtained was 100% with an average value of 81.13. The lowest value is 77.62 and the highest value is 89.52. This is in accordance with the expected because the expected results after achieving the expected completeness> 80%, with teacher grades> 68.75.